The crusades and the Christian world of the East: rough tolerance - MacEvitt, Christopher (The middle ages series, 2008)
Satan unleashed : the Christian Levant in the eleventh century -- Close encounters of the ambiguous kind : when Crusaders and locals meet -- Images of authority in Edessa, 1100-1150 -- Rough tolerance and ecclesiastical ignorance -- The legal and social staus of local inhabitants in the Frankish Levant -- The price of unity : ecumenical negotiations and the end of rough tolerance